THE EFFECT OF SELF-CONCEPT ON THE MATHEMATICS LEARNING ACHIEVEMENT - Rosliana Siregar; Fadhila Humairo (State Islamic University of North Sumatra Indonesia, 2018)
This study aims to determine the effect of self-concepts on mathematics learning achievement of students of class X at State Senior High School 14 Medan. The population in this study is all students of class X State Senior High School 14 Medan which amounted to 304 students. Technique of sampling using technique of Proportionate Stratified Random Sampling counted 40 student for research sample. Data collection using questionnaire method and documentation method. Data analysis technique used is regression analysis, correlation analysis and t test with significance level of 5%. Testing data in this study using the help of SPSS 15 for Windows program for each test result. The results showed that there is a significant influence between self-concept and mathematics learning achievement obtained from the t count (3,572)> t table (1.68), with a probability significance of 0.01 <0.05. The magnitude of the determination coefficient of 25.1%.